Green synthesis of self-oriented flower-like Ag@Ag2O nanostructures functionalized with L-Tryptophan for colorimetric simultaneous determination of ultra-trace level of thiamin and riboflavin - Maryam Abbasi Tarighat; Zahra Khosravani; Gholamreza Abdi (Amino Acids)
Abstract The study focuses on the green synthesis of Ag@Ag2O nanostructures using Padina algae extract and functionalizing them with L-tryptophan to enhance their properties as a colorimetric sensor for simultaneous detection of ultra-trace levels of thiamin and riboflavin. The nanostructures are characterized using techniques like XRD, FESEM, FTIR, TEM, AFM, and DLS to understand their morphology, structure, and interactions with target molecules. FESEM analysis revealed the hierarchical flower-like Ag@Ag2O nanostructures. The TEM image shows the formation of core-shell nanostructures. Also, DLS analysis and surface zeta potential spectra illustrated the aggregated nature of fabricated nanocomposites in the presence of vitamins. The study is the first to report simultaneous determination of thiamin and riboflavin using a colorimetric sensor based on Ag@Ag2O-L-Try nanocomposites using partial leas square (PLS). The dynamic range of thiamin and riboflavin was achieved in 0.1 mol L−1 acetate buffer pH 4 and the ratio Ag@Ag2O: L-try 1:1. The Ag@Ag2O-L-Try sensor exhibited two linear ranges of 0.1- 1.0 and 3-350 µMol L− 1 for riboflavin and a linear range 3.0–60 µMol L− 1 for thiamin. Also, low detection limit of 1.92 µMol L− 1 and 0.048 µMol L− 1 was obtained for riboflavin and thiamin, respectively. The results indicated that the success of the method depends on the selective and sensitive colorimetric assay of the sensor along with the simultaneous determination by the PLS algorithm. Hence, the proposed technique can be used for the accurate and precise determination of vitamins in different pharmaceutical syrup and tablet samples.